The effectiveness of a rotavirus vaccine in preventing hospitalizations and deaths presumably due to acute infectious diarrhea in Brazilian children: a quasi-experimental study - Teles,Estêvão (2015)
INTRODUCTION: Rotavirus is the main etiologic agent of acute infectious diarrhea in children worldwide. Considering that a rotavirus vaccine (G1P8, strain RIX4414) was added to the Brazilian vaccination schedule in 2006, we aimed to study its effectiveness and safety regarding intestinal intussusception. METHODS: A quasi-experimental trial was performed in which the primary outcome was the number of hospitalizations that were presumably due to acute infectious diarrhea per 100,000 children at risk (0-4 years old). The secondary outcomes included mortality due to acute infectious diarrhea and the intestinal intussusception rates in children in the same age range. We analyzed three scenarios: Health Division XIII of the State of São Paulo (DRS XIII) from 2002 to 2008, the State of São Paulo, and Brazil from 2002 to 2012. RESULTS: The averages of the hospitalization rates for 100,000 children in the pre- and post-vaccination periods were 1,413 and 959, respectively, for DRS XIII (RR=0.67), 312 and 249, respectively, for the State of São Paulo (RR=0.79), and 718 and 576, respectively, for Brazil (RR=0.8). The mortality rate per 100,000 children in the pre- and post-vaccination periods was 2.0 and 1.3, respectively, for DRS XIII (RR=0.66), 5.5 and 2.5, respectively, for the State of São Paulo (RR=0.47), and 15.0 and 8.0, respectively, for Brazil (RR=0.53). The average annual rates of intussusception for 100,000 children in DRS XIII were 28.0 and 22.0 (RR=0.77) in the pre- and post-vaccination periods, respectively. CONCLUSIONS: A monovalent rotavirus vaccine was demonstrated to be effective in preventing the hospitalizations and deaths of children that were presumably due to acute infectious diarrhea, without increasing the risk of intestinal intussusception.